An examination of contemporary works for wind band and chamber ensemble: “Night dances for wind ensemble” by Bruce Yurko, “Simple gifts: four Shaker songs” by Frank Ticheli, and “Octet in E-flat, Op. 103” by Ludwig van Beethoven - Wimmer, Alexander Minh (Kansas State University, 2014)
The following report provides a comprehensive analysis of two works for wind band and one small chamber work for woodwind octet: Night Dances for Wind Ensemble by Bruce Yurko, Octet in E-flat Major, Op. 103 by Ludwig van Beethoven, and Simple Gifts: Four Shaker Songs by Frank Ticheli. This analysis provides information necessary for a conductor’s rehearsal preparation. Included is biographical information about the composer and a historical perspective of the composition itself. Highlighted are the technical difficulties, stylistic concerns, musical elements, and form and structure of each composition. As the researcher, my music education mission statement and perspective on quality literature selection are also included. Suggested listening, seating charts, acoustical justifications, and rehearsal plans with researcher evaluations are provided. The compilation of this information will allow conductors to make more informed musical decisions during their preparation and performances of the works.
Keywords: Bruce Yurko; Ludwig van Beethoven; Frank Ticheli; Conducting; Analysis; Masters report; Music (0413); Musical Performances (0943); Music Education (0522)